2010
DOI: 10.1186/1748-5908-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge transfer for the management of dementia: a cluster-randomised trial of blended learning in general practice

Abstract: BackgroundThe implementation of new medical knowledge into general practice is a complex process. Blended learning may offer an effective and efficient educational intervention to reduce the knowledge-to-practice gap. The aim of this study was to compare knowledge acquisition about dementia management between a blended learning approach using online modules in addition to quality circles (QCs) and QCs alone.MethodsIn this cluster-randomised trial with QCs as clusters and general practitioners (GPs) as particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
382
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 278 publications
(384 citation statements)
references
References 61 publications
(100 reference statements)
1
382
0
1
Order By: Relevance
“…In studies of the facilitated or small-group educational strategies, qualitative analysis of facilitated learning suggested that it can improve knowledge and self-directed learning, 15 while practicebased workshops and decision-support software appeared to improve the detection rate but not the management, in a trial of Blended learning techniques only demonstrated a significant improvement in knowledge gain when GPs self-reported using the online modules. 20 Among interventions that altered the care pathway, the trial of an in-home assessment of patients' mental wellbeing and functional capacity showed a significant improvement in detection rates. 23 Two studies of case management demonstrated improved management either by providing care more adherent to guidelines, increasing referrals to community services, and increasing anti-cholinesterase prescribing, 24 or by reducing hospital use and consultation rates with physicians, and by decreasing feelings of depression or isolation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies of the facilitated or small-group educational strategies, qualitative analysis of facilitated learning suggested that it can improve knowledge and self-directed learning, 15 while practicebased workshops and decision-support software appeared to improve the detection rate but not the management, in a trial of Blended learning techniques only demonstrated a significant improvement in knowledge gain when GPs self-reported using the online modules. 20 Among interventions that altered the care pathway, the trial of an in-home assessment of patients' mental wellbeing and functional capacity showed a significant improvement in detection rates. 23 Two studies of case management demonstrated improved management either by providing care more adherent to guidelines, increasing referrals to community services, and increasing anti-cholinesterase prescribing, 24 or by reducing hospital use and consultation rates with physicians, and by decreasing feelings of depression or isolation.…”
Section: Resultsmentioning
confidence: 99%
“…This found that both 'blended learning' and classical learning methods improved knowledge in these areas, but no significant difference between the groups was found, although a subgroup analysis showed that when GPs self-reported as having used the e-learning modules, their knowledge gain was significantly better than the other group's (an increase in knowledge score of 1.17, 95% confidence interval [CI] = 0.20 to 2.14, P = 0.019). 20 Four of the educational intervention studies investigated facilitated or smallgroup teaching. Facilitated learning can be described as an educational process wherein the learners are actively involved by collaborating and negotiating in all components of their own learning.…”
Section: Educational Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In face-to-face with online learning, and only two studies [98,104], compared blended with face-toface learning. There were no studies comparing blended with online learning only.…”
Section: Populationsmentioning
confidence: 99%
“…Four studies were from Europe, with one, [103] being conducted amongst general practitioners (GPs) from central London and Scotland, another, [3] with GPs working in the NHS across Spain, the third, [104] through primary care quality circles in Western Germany and the last [105] being conducted with occupational physicians through the Amsterdam University, Netherlands.…”
Section: Settingsmentioning
confidence: 99%